Improving Understanding of Prayer Material Through Audio Visual Media for SDN Lamklat Students - Masrul (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in learning Islamic religious education by using audio visual. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research are primary school students. The data of this research was obtained with test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with research success indicators. The results of the research show that audio visuals can improve student learning outcomes in learning Islamic religious education. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 45.91%, the first cycle 79.39% and in the second cycle it increased to 90.66%. Thus, the use of audio visual can be used as one of the alternatives to improve student learning outcomes in learning Islamic religious education.